Cellular and Molecular Requirements for Association of the Murine Cytomegalovirus Protein m4/gp34 with Major Histocompatibility Complex Class I Molecules - Lu, Xiuju (American Society for Microbiology, 2006)
The murine cytomegalovirus (MCMV) protein m4/gp34 is unique among known viral genes that target the major histocompatibility complex (MHC) class I pathway of antigen presentation in the following two ways: it is found in association with class I MHC molecules at the cell surface, and it inhibits antigen presentation without reducing cell surface class I levels. The current study was undertaken to define more clearly the structural and cellular requirements for m4/gp34 association with the MHC class I molecule K(b). We first assessed the role of the peptide-loading complex in m4/gp34-K(b) association, using cell lines lacking TAP, tapasin, or β(2)m. m4/gp34-K(b) complexes formed in the absence of TAP or tapasin, although not as efficiently as in wild-type cells. The expression of full-length and truncation mutants of m4/gp34 in a gutless adenovirus vector revealed that the transmembrane region of m4/gp34 was required for efficient association with the K(b) heavy chain. However, the peptide-loading complex was not absolutely required for the association, since m4/gp34 readily formed complexes with K(b) in detergent lysates. The addition of K(b)-binding peptide to the detergent lysates facilitated but was not essential for the formation of the complexes. The ease of complex formation in detergent lysates contrasted with the small fractions of m4/gp34 and K(b) that form complexes in infected cells, suggesting that the endoplasmic reticulum (ER) environment restricts access of m4/gp34 to K(b). Finally, although m4/gp34-K(b) complexes could form when m4 was carried either by MCMV or by the adenovirus vector, they were only efficiently exported from the ER in MCMV-infected cells, suggesting that MCMV provides additional factors needed for transport of the complexes.